Pengaruh Latihan Menggosok Gigi terhadap Perilaku Menggosok Gigi Pada Anak Usia Prasekolah - Vera Elisa Widia Wati; Roisah Roisah; Grido Handoko Sriyono (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Preschool-aged children are susceptible to dental issues, and improper tooth brushing may lead to dental caries. Behavior, a response to stimuli, is influenced by knowledge, impacting positive toothbrushing behavior. This study aimed to assess the impact of tooth brushing practice on preschool-aged children (3-6 years) at PGRI 5 Kapongan, Kandang Village, Kapongan District, Situbondo Regency. The research employed an experimental design with a single-group pre and post-test, involving a population of 38 preschoolers at Kindergarten PGRI, Kandang Village. A non-probability purposive sampling technique was used to select 35 participants, with observations recorded using an observation sheet. The Wilcoxon matched statistical test yielded a p-value of 0.000 ? ? 0.005, indicating significance. Initially, 65.7% of respondents exhibited suboptimal tooth brushing (not quite right), but after intervention, 91.4% demonstrated proper brushing behavior. The Wilcoxon matched statistical test confirmed significance (p-value 0.000 ? ? 0.005). In conclusion, H1 is accepted, signifying the influence of tooth brushing practice on tooth brushing behavior in preschool-aged children. This insight into toothbrushing is anticipated to cultivate positive behavior, promoting oral health and mitigating dental diseases among children.